FORMULATION OF THE DEVELOPMENT STRATEGY OF AN ORGANIZATION USING A SWOT ANALYSIS - Arys Susanto; Arica Dwi Susanto; Avando Bastari (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
This requires an organization to be able to compete by always paying attention to the user's condition. Development strategy is one way to find out competitiveness in each of its power lines. To deal with user competition, especially in the face of global users, an organization must be able to establish a method as the basic foundation for the formulation of development strategies by increasing the value of competitiveness for its output or services. This strategy needs to be involved using the SWOT method as the main method to increase output, internal and external factors become the initial steps to carry out strategies to optimize business to achieve success. The use of an effective SWOT analysis can play an important role in determining the development strategy, in order to know the strengths, weaknesses, opportunities and threats faced by the company in maintaining the survival and continuity of the organization. The problem that the answer in this research is looking for is whether the SWOT analysis is the right strategy to increase output in the organization and how the development strategy applied by the organization in overcoming global friendships. In connection with these problems the following hypothesis is proposed: It is suspected that using a SWOT analysis can increase output so that the organization experiences a profit (surplus). This study uses primary data by providing questionnaires and secondary data to obtain archives or documents. In line with the problem and the research hypothesis, this study was conducted using the IFAS analysis method to analyze internal factors, EFAS analysis for external factors, then, included in the quantitative model, namely the SWOT matrix. The results of the analysis show that, using IFAS and EFAS analysis and using SWOT analysis shows the position of the organization in cell 2, the strategy chosen to support the achievement of the objectives of the organization is ST strategy.Keywords: SWOT, Strategy, Product Marketing, Business.